2018
DOI: 10.1016/j.nicl.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Lesion locations associated with persistent proprioceptive impairment in the upper limbs after stroke

Abstract: Proprioceptive deficits are common after stroke and have been associated with poorer recovery. Relatively little is known about the brain regions beyond primary somatosensory cortex that contribute to the percept of proprioception in humans. We examined a large sample (n = 153) of stroke survivors longitudinally to determine which brain regions were associated with persistent post-stroke proprioceptive deficits. A robotic exoskeleton quantified two components of proprioception, position sense and kinesthesia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 82 publications
2
85
0
Order By: Relevance
“…Furthermore, despite only few investigations into brain regions responsible for position sense in humans exist, recent studies identified that a distributed network of brain areas appear to be responsible for processing position sense (Findlater et al, 2016(Findlater et al, , 2018.…”
Section: Modulation Of the Difference Between Vp And P Condition Bymentioning
confidence: 99%
“…Furthermore, despite only few investigations into brain regions responsible for position sense in humans exist, recent studies identified that a distributed network of brain areas appear to be responsible for processing position sense (Findlater et al, 2016(Findlater et al, , 2018.…”
Section: Modulation Of the Difference Between Vp And P Condition Bymentioning
confidence: 99%
“…Lesions of the SMG and HG are known to lead to impairments in proprioceptive function (Findlater et al, , ; Kenzie et al, ). The SMG, as part of the parietal sensory association area, is an important region for integration of somatosensory information (Iwamura, ; Lynch, ; Pandya & Seltzer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not entirely surprising that damage to the tract communicating with the POCG-SMG was associated with poor proprioceptive performance in the present study. HG is involved in the frontoparietal network (Shinn, Baker, Cohen, & Ongur, 2013) and is known to contribute to the spatial localization of sound (Altmann et al, 2007;Zatorre & Penhune, 2001) but based on the results of Findlater et al (2018), it may also contribute to somatosensory processing. The present study adds to our previous results as lower FA in the POCG-HG was also associated with poor proprioceptive performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations